The effect of ECRH on the stability of the radiation induced m=2 mode and on the current quench of a major disruption - F. Salzedas (2002)
The results of a series of experiments done in RTP which had the purpose to avoid or ameliorate radiative density-limit disruptions, will be reported. Avoidance of disruptions was achieved by stabilizing the m = 2 radiation induced tearing mode (RTM) with electron cyclotron resonance heating (ECRH). Both continuous and modulated power deposition was studied. It was found that stabilization with modulated ECRH in phase with the O-point was less efficient than continuous ECRH, contrary to theoretical expectations. Detailed scans of the EC power deposition and of the power intensity were in agreement with the assumption that radiative heat loss is the driving mechanism of this m = 2 mode. Amelioration of disruptions was achieved, in a pilot experiment, by applying ECRH at the end of the energy quench. In this way, the current decay that follows a major density-limit disruption could be reversed.